2016
DOI: 10.1186/s40174-016-0062-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural unemployment after the crisis in Austria

Abstract: This paper analyzes the Austrian Beveridge curve as well as the Beveridge curves for different economic sectors in Austria over the period from 2008 onwards. We find significant outward shifts of the Beveridge curves in eight of the 21 sectors of the economy. We further analyze what factors have contributed to this change. Our results suggest that a significant part of the currently rising unemployment in Austria may be attributed to structural changes. Those structural changes mainly affect the four large sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
(9 reference statements)
1
8
1
Order By: Relevance
“…We can see a clear upward trend indicating that, at the end of the observed time period, the matching efficiency decreased and even led to an increase in the unemployment rate. This finding is consistent with the findings of Christl et al (2016), who reported that the average matching efficiency was stable until 2013 in Austria but has been steadily decreasing ever since.…”
Section: Decomposition Of Unemployment Ratesupporting
confidence: 93%
See 1 more Smart Citation
“…We can see a clear upward trend indicating that, at the end of the observed time period, the matching efficiency decreased and even led to an increase in the unemployment rate. This finding is consistent with the findings of Christl et al (2016), who reported that the average matching efficiency was stable until 2013 in Austria but has been steadily decreasing ever since.…”
Section: Decomposition Of Unemployment Ratesupporting
confidence: 93%
“…Several studies have discussed the Austrian Beveridge curve developments after the Great Recession, e.g, Bonthuis et al (2013Bonthuis et al ( , 2015 but found no significant shift of the Beveridge curve in Austria. However, Christl et al (2016) found a statistically significant shift in the long-term Beveridge curve in Austria after 2014, which according to them occurred in the four main sectors: construction, wholesale, transportation, and accommodation and food service activities. In line with Böheim (2017) 2 , the authors attribute the shift to a decrease in the matching efficiency.…”
Section: Literature Overviewmentioning
confidence: 93%
“…With an unemployment rate of 4.3%, it is well below the EU average. Unemployment has the character of structural unemployment (Christl, M., Köppl -Turyna, M.;Kucsera, D. (2016)). One of the reasons for low unemployment is the dual education system (Graf, L. (2016)), which guarantees the industry a supply of skilled labor from apprentices and industrialists.…”
Section: Realities Of the Economy Of The Republic Of Austriamentioning
confidence: 99%
“…Schiman (2018) argues in a macro-model framework that the Austrian Beveridge curve shifted due to a labour supply shock caused by the opening of the labour market to several Eastern European countries after 2008. However, Christl et al (2016) and later Christl (2020) using detailed data labour-market transition argue that the shift was caused primarily by an increase in labour market mismatch.…”
Section: Introductionmentioning
confidence: 99%